UPACARA MAAYU-AYU DI PURA BALE MAS DESA PAKRAMAN SUDAJI KECAMATAN SAWAN KABUPATEN BULELENG (Perspektif Bentuk Fungsi dan Makna) - Ketut Agus Nova (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Maayu-ayu Ceremony is held at Bale Mas Temple Pakraman Sudaji Village, Sawan Subdistrict, Buleleng Regency every year which falls on Purnama Sasih kaulu to Purnama Sasih Kasanga. Maayu-ayu Ceremony is a religious ceremony to be carried out as a series of ceremonies aimed at getting the good and achieve happiness in a celebration. Maayu-ayu ceremony in Bale Mas Temple has a uniqueness that can be seen in Maayu-ayu ceremony, namely Maayu-ayu ceremony is held for 30 consecutive days from Purnama Sasih kaulu to Purnama Sasih Kasanga. The results are (1) the Maayu-ayu Ceremony starts from the Pujawali Ceremony, then the Maayu-ayu Ceremony in the afternoon and the Nyineb Ceremony at the end of the Maayu-ayu Ceremony. (2) The function of the Maayu-ayu ceremony at Bale Mas Temple consists of Social Functions, The function of ritual / religious, and the function of preservation. The meaning of Maayu-ayu ceremony in Bale Mas Temple consists of the meaning of preservation of art and culture, the meaning of Unity, the Meaning of Balance which is the balance of Man and God, The Meaning of Maayu-ayu Ceremony includes: (a) Ethical value, which is moral knowledge shown by the people of Sudaji Village, (b) Aesthetic Value, namely the beauty value contained in the Maayu-ayu Ceremony can be seen from the facilities used, (c) Religious social values, namely the mutual mutual cooperation attitude of the Sudaji Village community and (d) the Divine Value, the Maayu-ayu Ceremony, is carried out because of trust society towards God Almighty and their manifestations.